(untitled) (International Current Pharmaceutical Journal, 2016)
The present study focussed on the bactericidal effect of Tridax procumbens L. against water borne bacterial pathogens. The bacterial species used in present study were Escherichia coli, Vibrio cholerae, Salmonella typhimurium and Klebsiella pneumoniae, which cause serious diseases like Diarrhoea, Cholera, Salmonellosis, Pneumonia, etc. CLSI recommended broth microdilution method was used in this study for assessing the antibacterial efficacy of the candidate plant extract. Results were depicted in the form of IC50 (mg/ml) and MIC (mg/ml) values. On the basis of this study it can be interpreted that Tridax procumbens L. proved to be a very potential source of antibacterial agent against some water borne bacterial. Pandey et al., International Current Pharmaceutical Journal, February 2016, 5(3): 22-26